Thrombocytopenia Rates In Newborns Diagnosed With Gram-Negative Sepsis. Insights From NICU Experimental Based Study - Sobia Shahalam; Madiha Iqbal; Sara Hassan; Shazia Rizwan; Rizwan Waseem; Rabeya Rehman (Journal of Rawalpindi Medical College)
Objective: To evaluate the prevalence of thrombocytopenia observed in neonates admitted to the hospital with sepsis.